The Limpopo Low-Level Jet: mean climatology and role in water vapor transport - Spavins‐Hicks, ZD; Washington, R; Munday, C (American Geophysical Union, 2021)
Low-level jets (LLJs) are well established as critical features of regional climates globally. However, across sub-Saharan Africa, LLJs have received relatively little attention, in part due to a lack of data. Utilizing high-resolution reanalysis data, this paper develops the first climatology of a neglected feature of the southern African circulation – the Limpopo LLJ – and investigates its role in delivering water vapor to the continental interior. We demonstrate that the LLJ has a clear diurnal cycle and is a regular feature of the circulation throughout the year, forming on 80.9% of days. The pressure gradient between southern Mozambique and the continental interior acts as a first-order control on the annual cycle of jet strength, which peaks in October, achieving average maximum windspeeds of 15.8 m.s−1 at the core. Water vapor transport follows the same clear diurnal cycle, with at least 72% occurring over 18:00–08:00, and is closely related to jet strength: On average the strongest jet events advect 1.04 × 1012 kg (1.02 × 1012 kg) more moisture each night than the weakest in October-December (January-March). Strong jet events are typically linked to ridging anticyclones along the east coast of South Africa and are associated with increased rainfall in central and southern Botswana and northern South Africa the following day.